Empowering career pathways: integrating self-regulation strategies with career counseling practices - Rezaiee, Mohsen; Kareshki, Hossein (Frontiers in Education, 2024)
IntroductionThis study explores the integration of self-regulation strategies into career counseling to enhance career development. It outlines the rationale behind this integration and sets the objectives of providing practical strategies for educators and counselors to support career paths.MethodsThe theoretical framework examines the role of self-regulation in career development and its intersection with career counseling in the modern workforce. Practical applications include self-regulation techniques for career advancement, career counseling interventions, and case studies.ResultsThe application of these strategies is compiled into a resource manual, which includes tools, assessments, and activities for clients, as well as resources for career counselors. This manual serves as a practical toolkit for implementing the guide's recommendations.DiscussionThe conclusion highlights the contributions of the guide, reflecting on the integration of self-regulation and career counseling. Policy implications are discussed, with recommendations for education and workforce development, advocating for the institutionalization of self-regulation in career services. Future research and policy directions are suggested, emphasizing the importance of this integration for educational achievement and personal satisfaction. Overall, the guide offers a novel approach to career counseling, grounded in self-regulation theory and practice, providing a comprehensive resource for enhancing career pathways.